Stability Derivatives Cast in the Frame of Subsonic Unsteady Aerodynamics - Nowak, M. (Engineering Transactions, 1998)
On the basis of numerical results and theoretical considerations, a general form of the (unsteady) linear, discretized aerodynamic operator in the Laplace- and in the time-domain, for two- and three-dimensional subsonic flow is proposed. It corresponds to the classical Theodorsen solution for an airfoil in incompressible flow. The model of aerodynamic derivatives uses a polynomial approximation to the transfer functions. There are identified terms, which are neglected in this approach: these are the deficiency function and, in the case of compressible fluid, also the term responsible for the initial pulse. These results clears the limitations and possible improvements of the aerodynamic derivatives model.